EKSISTENSI PERTUNJUKAN DAN KONSEP DALAM BERKARYA SOLO BEATBOX COMMUNITY - Wari, Tantri Nindyas (Institut Seni Indonesia (ISI) Surakarta, 2019)
The music carried by the Solo Beatbox Community has its own attraction in the form of a musical imitation of a show. Imitating the sound of musical instruments with mouth, i.e. playing music without using real musical instruments, the sound produced was almost indistinguishable to that of the original instrument. This uniqueness raises the aspects regarding the existence of the group’s performances whose by all means are inseparable from the works presented to the audience. Social media plays an important role in the development of their community, from promotions to publications on the Solo Beatbox Community. In order to get their stage, the Solo Beatbox Community uses the gethok tular (‘word of mouth’, ‘viva voice’) method to facilitate their access toward the upcoming shows. Member regeneration is also one of the efforts to prevent this community from dying out. They have elements in the conceptualization of their work that is based on the type and concept of the event in question, as well as the musical trends that are popular with the public. This triggered the existence of the Solo Beatbox Community show.Keywords: Solo Beatbox Community, The concept of creating Solo Beatbox Community.